Placenta Previa, Percreta – A Case Report of Successful Management - Begum, Sartaj; Sharmin, Shanzida; Parvin, Maleka; Majumder, Shima; Naher, Akterun; Parvin, Tahamina; Akter, Romena; Zafrin, Rummana (Journal of Comilla Medical College Teachers’ Association, 2023)
Background: Placenta percreta is a rare complication of pregnancy and is associated with significant postpartum hemorrhage. Incidence of morbidadherant placenta has dramatically increased due to increasing caesarean section rate all over the world. Placenta percreta is the most severe form of morbid adherent placenta. It frequently results in maternal morbidity and mortality which is mainly caused by massive obstetric hemorrhage emergency hysterectomy. Majority of these cases are seen in patient with history of previous LSCS with anterior low lying placenta. Here we present a case of placenta in lower segment with percreta in a women with H/O previous 2 C/S with large fibroid in fundus. J Com Med Col Teachers Asso Jan 2023; 27(1): 34-37